Theory of periodic structures in lipid bilayer membranes - Falkovitz, Meira S. (1982)
An approximate, new model for the structure of the periodic, undulated P(β′), phase of phosphatidylcholine bilayers is proposed. The properties of this phase are deduced by minimizing a Landau-de Gennes expression for the bilayer free energy when this free energy contains a term favoring a spontaneous curvature of the membrane. The theoretical calculation leads to a model for the P(β′) phase of phosphatidylcholine bilayers having a number of novel physical properties, including periodic variations in membrane “fluidity.”